Hak Privasi sebagai Hak Konstitusional di Era Digital: Kajian Yuridis dalam Perspektif Hukum Siber - Qurrotuaini, Nur Azizah (UIN Sunan Kalijaga Yogyakarta, 2024)
The rapid development of digital technology has brought convenience to various aspects of life. On the other hand, this development also raises new challenges, especially related to the protection of the right to privacy. Protection of the right to privacy in Indonesia has been regulated in various laws and regulations, including Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. However, the rapid development of technology often exceeds the speed of regulation formation. Where this right is often threatened by various activities in cyberspace. Problems such as cross-border data protection, the use of new technologies (for example: artificial intelligence), and the involvement of non-institutional entities in managing personal data are very hot topics. Through an in-depth study related to the legal analysis of the protection of the right to privacy in the digital era, especially cyber law, it can identify international and national legal instruments, relevant human rights principles and legal efforts made to overcome them. In addition, the results of the study can see the extent to which existing regulations are able to provide adequate protection for the right to privacy. Abstrak Perkembangan tekonologi digital yang pesat telah membawa kemudahan dalam berbagai aspek kehidupan. Di sisi lain, perkembangan ini juga menimbulkan tantangan baru, terutama terkait dengan perlindungan hak atas privasi. Perlindungan hak atas privasi di Indonesia telah diatur dalam berbagai peraturan perundang – undangan, termasuk Undang – Undang Nomor 19 Tahun 2016 tentang perubahan atas Undang – Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik. Namun, perkembangan teknologi yang begitu cepat seringkali melampaui kecepatan pembentukan regulasi. Dimana hak ini seringkali terancam oleh berbagai aktivitas di dunia maya. Adapun masalah-masalah seperti perlindungan data lintas batas, penggunaan teknologi baru (contoh: kecerdasaan buatan), serta keterlibatan entitas non lembaga dalam penggelolaan data pribadi menjadi pembahasan yang sangat hangat. Melalui kajian mendalam terkait analisis yuridis mengenai perlindungan hak atas privasi dalam era digital, khususnya hukum cyber, dapat mengidentifikan instrument hukum internasional dan nasional, prinsip hak asasi manusia yang relevan dan upaya hukum yang dilakukan untuk mengatasinya. Selain itu, hasil penelitian dapat melihat sejauh mana regulasi yang ada mampu memberikan perlindungan yang memadai terhadap hak atas privasi